A GAME-THEORETIC ANALYSIS OF PASCAL'S WAGER. (4th September 2017) - Tarar, Ahmer
Abstract: Formal analyses of Pascal's Wager have almost all been decision-theoretic, with a human as the sole decision-maker. This paper analyses Pascal's Wager in a game-theoretic setting in which the deity whose existence the human is considering wagering on is also a decision-maker. There is an equilibrium in which the human chooses to wager that the deity exists and Pascal's Wager thus operates, but also one in which the human does not wager. Thus, in a game-theoretic setting, Pascal's Wager is indeterminate: wagering and not wagering are both consistent with equilibrium behaviour.